Pengaruh Anggaran Pendapatan dan Belanja Negara Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2015-2024 - Lastaria Br Sinaga; Irsad Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of the State Budget (Anggaran Pendapatan dan Belanja Negara/APBN) on Indonesia’s economic growth during the period 2015–2024. Economic growth is measured by real Gross Domestic Product (GDP) growth, while fiscal variables are represented by government expenditure and government revenue. This research employs a quantitative approach using time series data sourced from Statistics Indonesia (BPS) and the Ministry of Finance of the Republic of Indonesia. The analytical method used is multiple linear regression. The results show that government expenditure has a positive and significant effect on economic growth, while government revenue contributes to economic growth through its role in maintaining fiscal sustainability. The findings confirm the important role of fiscal policy through APBN as a countercyclical instrument in supporting economic stability and growth, particularly during periods of economic shock such as the COVID-19 pandemic.